How could one prove by induction that: $$\forall{n}\in{N}:1(1!)+2(2!)+3(3!)+...+n(n!)=(n+1)!-1$$
My attempt so far:
Base case: Let n = 1, 1(1!) = (2)! - 1 = 1, holds true for LHS = RHS.
Inductive hypothesis: Assume true for n=k, such that:
$$\forall{k}\in{N}:1(1!)+2(2!)+3(3!)+...+k(k!)=(k+1)!-1$$
Inductive step: Let n = k + 1:
$$(k+2)! - 1 = (k+2)(k+1)! - 1 = (k+2)(k+1)(k)! - 1$$
...And now I'm stuck. The fact that the LHS is a summation throws me off, and can't seem to figure out how to continue (or whether I even worked with the "more correct" side of the equation).
You're on the right track but we need to use our assumption. I also prefer starting with the complicated side.
$\Sigma_{i=1}^{k+1} (i*(i!))=(k+1)(k+1)!+\Sigma_{i=1}^{k} (i*(i!))=(k+1)(k+1)!+(k+1)!-1=(k+1+1)(k+1)!-1=(k+2)!-1$